Additive manufacturing TPMS lattice structures: Experimental study on airflow resistivity - Ganesh Chouhan; BalaMurali Gunji (Results in Materials, 2023)
Triply periodic minimal surface structures (TPMS) are continuously adopted in the architectural engineering and aircraft sectors in pursuit of noise mitigation. The airflow resistivity significantly influences the acoustic performance of lattice structures. The present work is a step toward designing appropriate structures of TPMS to obtain desired acoustics performance using the standard of ISO 9053–1:2018(E). In this work, the four TPMS lattices Gyroid, Diamond, Lidinoid, and Split P have been designed with three different parameters (porosity, sample length, and diameter) to predict the airflow resistivity and pressure drop of the structures. Various experiment sets were conducted on customized airflow resistivity experimental apparatus for cylindrical lattices with multiple parameters to identify the most effective lattice structures. Based on the findings, it was observed that lattice structures with less porosity, sample length, and sample diameter depict the highest level of airflow resistivity and pressure drop. However, for all four lattices, close differences in airflow resistivity values were noticed.